The Role of Parents in Improving Character Education during Covid-19 Pandemic - Ruzaini Ruzaini; Nurhalin Nurhalin (Akademika: Jurnal Keagamaan dan Pendidikan, 2020)
Covid-19 has a major impact on all sectors of public life, including the education sector. It is an important sector that supports all types of academic activities. Covid-19 forces the government to close all schools and start implementing distance learning. This certainly raises several views, because not all schools in Indonesia can effectively implement distance learning. To overcome this problem, cooperation between several parties is required. Especially the role of parents who must be more active at home to replace the role of teachers at school. The role of parents is expected to be able to provide a good teaching and learning atmosphere at home. The focused on this problem is the character development of children during the covid-19 pandemic. Parents must be able to provide examples and guidance about character circles, which children learn from parents through sense senses. Therefore, parents must be able to set a good example before giving character education to children at home.